Internet of Things (Iot)-based Overcurrent Protection and Detection Device for Household Eletrical Safety - Muliadi; Muhammad Mahdinul Bahar; Aulia Sabril; Muhammad Riska (Program Studi Teknik Komputer, 2025)
The increasing risk of electrical fires caused by overcurrent, overheating cables, and the lack of early monitoring mechanisms in conventional household electrical protection systems has become a significant safety concern, as most protection devices only disconnect power without providing real-time monitoring or early warnings. This study aims to develop an Internet of Things (IoT)-based electrical protection system capable of detecting abnormal electrical conditions and providing early warning notifications. The system uses an ESP32 microcontroller integrated with several sensors, including the PZEM-004T sensor to monitor electrical parameters, the DS18B20 sensor to detect cable temperature, the MQ-2 sensor for smoke detection, and a flame sensor for fire detection. The research methodology includes system design, hardware and software integration, and performance testing through sensor functionality tests and response time measurements. The testing results show that the PZEM-004T sensor measured voltage in the range of 212.50–213.60 V and current around 1.95–1.96 A during testing. The DS18B20 sensor recorded temperatures between 27.81°C and 28.94°C with an average response time of 12.05 seconds when the threshold was exceeded. The MQ-2 sensor achieved a 100% success rate in detecting smoke, while the flame sensor detected fire in approximately 85% of the trials, with response times of 1.4 seconds and 1.7 seconds before triggering automatic power disconnection via a relay. The system also transmitted monitoring data and warning notifications through a web application and Telegram using cloud-based IoT communication, demonstrating its potential to improve household electrical safety through integrated monitoring, automatic protection, and early warning notifications.